Properties of acoustic barriers in a field of reflected waves - CZARNECKI, Stefan; KOTARBIŃSKA, Ewa (Archives of Acoustics, 1976)
This paper deals with the effect of selected factors on the properties of acoustic barriers. Most attention has been paid to the influence of reflected waves which diminish the effectiveness of a barrier for the area behind it. The considerations were limited to interiors with an extended ceiling and for cases involving one or a few noise sources. Such conditions occur often in industrial halls and in urban areas. Under these circumstances the condition of equal energy density distribution is not fulfilled, so the reverberation theory is not valid. Hence, the mirror method was used which constitutes an extension of the image source method by the mirror representation of all diffracting and absorbing surfaces. Analytical relations were obtained, which permit the calculation of the effect of the reflected waves in decreasing the insertion loss of a barrier. Two established criteria, spatial and energetic were used. The theoretical analysis was confirmed by experimental results.